Perancangan dan Implementasi Dashboard Keuangan Persekutuan Joy Indonesia dengan Metode User Centered Design - Erwin Prayoga; Rosa Delima (Fakultas Teknologi Informasi, 2022)
JOY Indonesia Fellowship is a non-profit organization based in the city of Yogyakarta. The JOY Indonesia Fellowship is engaged in Christian and Catholic student services whose members are university students and college students in Yogyakarta. The finances of the JOY Indonesia Fellowship are fully supported by the alumni of this organization themselves and supporters from Korea. Financial management is fully carried out by management staff. Until now, financial management is still using excel and reporting is still in the form of PDF files which are usually published on the fellowship website at the beginning of every month. This makes alumni and supporters not know important information such as which funds are more prioritized to support or which funds have not reached the budget target. The purpose of this study is to develop a web-based dashboard with a user-centered design (UCD) method that helps the management staff of the JOY Indonesia Fellowship in managing financial data and makes it easier for alumni and supporters to monitor the fellowship's finances. This study resulted in a financial dashboard for the JOY partnership. The development process using the UCD method is carried out in two iterations. The dashboard test involved fifteen respondents consisting of five staff respondents and ten alumni respondents. The test results show that the dashboard is effectively used to present financial information to support the board in managing the organization's finances.